Con-T[M8Q] potently attenuates the expression and development of morphine tolerance in mice. (15th June 2015) - Ren, Baolan; Zhou, Zhijie; Liu, Zhuguo; Li, Bailin; Ou, Jie; Dai, Qiuyun
Highlights: Con-T[M8Q] is a specific NMDA receptor NR2B inhibitor. Con-T[M8Q] potently inhibits the expression and development of morphine analgesic tolerance at low doses (5–20 nmol/kg). Con-T[M8Q] is more potent than ifenprodil, a small-molecule antagonist of the NMDAR. Con-T[M8Q] displays no drug resistance to morphine. Abstract: As a variant of peptide conantokin-T (con-T), con-T[M8Q] is derived from the venom of Conus tulipa . Our previous study has demonstrated that con-T[M8Q] selectively targets N -methyl-d -aspartate receptor (NMDAR) NR2B subunit. In the present study, we determined the effects of con-T[M8Q] on the expression and development of morphine tolerance using hot plate test and acetic acid writhing test. Our results demonstrated that con-T[M8Q] could efficiently attenuate the expression and development of morphine analgesic tolerance in mice at low doses (5–20 nmol/kg), and it exhibited more potent effects compared with ifenprodil, a typical small-molecule antagonist of NMDAR. In addition, low doses of con-T[M8Q] (5–20 nmol/kg) did not cause drug resistance and apparent analgesic activity compared with morphine. Taken together, con-T[M8Q] could be a promising new candidate in attenuating morphine tolerance.